Military-political rivalry of Ghurids with Seljukids in the middle of the 12th century - Sharipov Muhammad Marufovich (Studia Humanitatis, 2022)
Designing on the premise of written sources and scientific literature referring to the Soviet and post-Soviet period, the author makes an endeavour to highlight the military-political rivalry between the Tajik state of Ghurids and Seljukids appertaining to the middle of the 12th century and the circumstances of the emergence of Ghurid state, for the first time in historiography. In the middle of the 12th century Ala-ad-Din Husayn as the famous Padishah of Ghurid state liquidated Ghaznavids empire. In addition, Ala-ad-Din managed to achieve independence from the Seljuk state. These factors became the reason for the development of the socio-economic, political and military spheres of Ghurid state. The middle of the 12th and the beginning of the 13th centuries are the heyday of Ghurid state.